Development of phenolic-modified activated carbon for reduced energy band gap and improved semiconductor performance - Rahmadanti Rahmadanti; Agung Sugeng Widodo; Sulistyono Sulistyono; Purnami Purnami (Politeknik Negeri Lhokseumawe, 2025)
This study aims to develop more efficient activated carbon-basedsemiconductor materials through modification with phenolic compounds to reduce the energy gap and increase adsorption capacity. Activated carbon was modified by adding phenolic compounds, then characterized using FTIR, UV-Vis, SEM, and EDS to analyze structural, morphological, and electronic changes. The UV-Vis characterization results showed that the AC 70 + F 30 sample experienced a wavelength shift towards the x-axis, which indicates a decrease in energy gap and is confirmed by Tauc plot analysis from 3.60 eV to 2.98 eV. SEM-EDS results revealed changes in pore morphology and a decrease in carbon content due to the interaction between activated carbon and phenolic compounds. These findings indicate that phenolic modification effectively reduces the energy gap and improved charge-transfer characteristics, thereby contributing to the development of more environmentally friendly and efficient activated carbon-based semiconductor materials.